Assessment of public awareness and perspectives towards adverse drug reaction reporting system in Karachi, Pakistan - Wajiha Iffat; Sadia Shakeel; Shagufta Nesar; Ambreen Qamar; Zille Huma; Hina Rehman; Mahwish Akhtar; Syed Ahsan Ali; Mohammad Nadeem Ansari; Muhammad Yaqoob; Areeb Bin Tariq (PLoS ONE, 2025)
Background Public involvement in reporting adverse drug reactions (ADRs) generates a broader database on drug safety. Underreporting remains a hindrance to implementing an effective pharmacovigilance system that ultimately affects public health. Hence, it is critical to appraise the public’s awareness of ADR reporting and pharmacovigilance to address the gaps for the enhancement of ADR reporting rate. Objectives The current study explored public knowledge and attitudes toward ADR reporting in Karachi, Pakistan. Methods A quantitative cross-sectional study was conducted from 3rd Jan 2022 to 30th Nov 2022 using a forty-item questionnaire to evaluate public insights regarding the ADR and its reporting. Descriptive analysis was executed to determine frequencies and percentages for the respondents’ baseline characteristics and the responses toward ADR reporting. The chi-square test (χ2) was applied to determine the association between the dependent and independent variables considering a p-value < 0.05 as statistically significant. Results The response rate of the present study was 78.3%. More than 80% of the respondents deemed that ADR occurs only with high doses of medicines and over-the-counter medications do not cause any ADR. More than 75% of the respondents did not know that the ADR reporting form is available on the Drug Regulatory Authority of Pakistan (DRAP) website; the response varied significantly with the education (p = 0.002) and social status (p = 0.0001) of the respondents. More than 50% of the participants refused to ever report an ADR to health professionals. Physicians (n = 364; 47.7%) and pharmacists (n = 253; 33.1%) were the respondents’ professed most reliable sources to whom ADR can be reported; responses varied significantly with their education (p = 0.003) and age (p = 0.001). Conclusions The study has provided insight into the challenges and gaps needed to improve ADR reporting in Pakistan. The outcomes revealed that the public is aware of the benefits of reporting ADRs; however, they do not realize their role and the potentially significant impact on the healthcare system by contributing to ADR reporting. Therefore, it is a need of time to educate the public on the value of reporting ADRs and implement user-friendly and accessible ADR reporting systems in patient care areas to facilitate easier reporting.